Non-pharmacological pain management strategies: Mechanism of action (non-pharmacological pain therapy) - Petrović Nataša Đ.; Lađević Nebojša; Jovanović Vesna; Jovičić Jelena; Lazić Miloš; Lađević Nikola (Serbian Journal of Anesthesia and Intensive Therapy)
Pain is a major health issue representing a leading cause of disability. It affects millions of adults worldwide and impose significant burdens on society, healthcare systems, and personal well-being. The management of chronic pain presents a major challenge for healthcare professionals, as there is no single or universally effective treatment. Conventional treatments such as opioids and nonsteroidal anti-inflammatory drugs are first line treatment, but they carry significant risks and limitations, including addiction, tolerance, dependence, adverse effects, especially when used long term. As a result, additional approaches are needed to provide effective and safe chronic pain relief. Non-pharmacological pain management strategies represent a promising domain especialy as a part of complementary tailored to individual needs and integrated to contemporary pain medicine.